Systematic review and meta-analysis of changes in quality of life following initiation of buprenorphine for opioid use disorder. (1st June 2022) - Golan, Olivia K.; Totaram, Rachel; Perry, Elizabeth; Fortson, Kennicia; Rivera-Atilano, Raul; Entress, Rebecca; Golan, Matthew; Andraka-Christou, Barbara; Whitaker, Daniel; Pigott, Therese
Abstract: Background: People with opioid use disorder (OUD) experience lower quality of life (QoL) than the general population, but buprenorphine treatment for OUD could help improve QoL of individuals with OUD. Thus, we conducted a systematic review and meta-analysis of the impact of buprenorphine on QoL among people with OUD. Methods: Seven databases were searched through August 2020. We included English-language studies with pre- and post- QoL assessments internationally. Standardized mean differences were calculated for five domains of QoL measures using a random effects model for correlated effect sizes with robust variance estimation. Meta-regression was used to assess variation in effect sizes based on QoL domain, treatment, and patient factors. Results: Twenty-one peer-reviewed studies from twelve countries were included. Only three studies included a no-treatment control group and five studies assigned groups using randomization. Improvements between baseline and follow-up were observed across all five domains of QoL measures (overall, physical, psychological, social, and environmental). The certainty of evidence was low for all domains of QoL, and very low for environmental QoL. We did not observe differences in the effect of buprenorphine on QoL by QoL domain, duration, dose, participant characteristics, or adjunctive counseling services. Conclusions: Buprenorphine treatment likely improves overall, physical, psychological, and social QoL, and may improve environmental QoL, for individuals with OUD. Findings are limited by study quality, including lack of control groups and incomplete reporting. Future studies with more rigorous methods and comprehensive reporting are needed. Highlights: Buprenorphine likely improves physical, psychological, and social quality of life. Buprenorphine may improve environmental quality of life (QoL). Certainty of the evidence was low, especially regarding environmental QoL. Change in QoL did not differ by duration, dose, or adjunctive counseling.